Does access to no-cost contraception change method selection among individuals who report difficulty paying for health-related care? - Alexandra Gero; Rebecca G. Simmons; Jessica N. Sanders; David K. Turok (BMC, 2022)
Abstract Background Out-of-pocket costs continue to be a barrier to accessing necessary healthcare services, including contraception. We explored how eliminating out-of-pocket cost affects contraceptive method choice among people reporting difficulty paying for healthcare in the previous year, and whether method satisfaction differed by method choice. Methods We used data from the HER Salt Lake Contraceptive Initiative. This prospective cohort study provided participants with no-cost contraception (April 2016-March 2017) following a control period that provided no reduction in cost for the contraceptive implant, a reduced price for the hormonal IUD, and a sliding scale that decreased to no-cost for the copper IUD (September 2015-March 2016). We restricted the study population to those who reported difficulty paying for healthcare in the past 12 months. For our primary outcome assessing changes in method selection between intervention and control periods, we ran simultaneous multivariable logistic regression models for each method, applying test corrections for multiple comparisons. Among participants who continued their method for 1 year, we explored differences in method satisfaction using multivariable logistic regression. Results Of the 1,029 participants reporting difficulty paying for healthcare and controlling for other factors, participants more frequently selected the implant (aOR 6.0, 95% CI 2.7, 13.2) and the hormonal IUD (aOR 3.2, 95% CI 1.7, 5.9) during the intervention than control period. Comparing the same periods, participants less frequently chose the injection (aOR 0.5, 95% CI 0.3, 0.8) and the pill (aOR 0.4, 95% CI 0.3, 0.6). We did not observe a difference in uptake of the copper IUD (aOR 2.0, 95% CI 1.0, 4.1).Contraceptive satisfaction scores differed minimally by contraceptive method used among contraceptive continuers (n = 534). Those who selected LNG IUDs were less likely to report low satisfaction with their method (aOR 0.5, 95% CI 0.3, 0.97). Conclusion With costs removed, participants who reported difficulty paying for healthcare were more likely to select hormonal IUDs and implants and less likely to select the injectable or contraceptive pills. Among continuers, there were few differences in method satisfaction. ClinicalTrials.gov Identifier NCT02734199